The Psychology of Grey in Painting Backgrounds / Aimi Atikah Roslan, Nurul Shima Taharuddin and Nizar Nazrin - Roslan, Aimi Atikah; Taharuddin, Nurul Shima; Nazrin, Nizar (Universiti Teknologi MARA, Perak, 2022)
This writing is about a study of the psychology of the colour grey used on the painting backgrounds. The study concerns how the colour grey affects the behaviour of artists and has an impact on the production of works of art. A descriptive research using qualitative research method through surveys and observations as instrument was carried out. The artist uses the colour grey as his guide in producing works to give a sense of emotional strength, feelings of melancholy, passion and so on. Each colour has a different psychological and emotional effect.